Protecting our vulnerable in the midst of the COVID-19 pandemic: lessons learnt from Malta. (September 2021) - Cuschieri, Sarah; Grech, Victor
Abstract: Objectives: COVID-19 is a health burden threatening the elderly and those with comorbidities. Malta is an ageing and cardiometabolic country. The study depicts how Malta protected the elderly and the effect of vaccination on this subpopulation. Study design: Observational study with quantitative analyses. Method: Data were obtained from Malta's COVID dashboard, Institute for Health Metrics and Evaluation and Maltese newspapers. The case-fatality ratio (CFR) and Years of Life Lost (YLLs) for COVID were calculated. Comparisons were made between COVID-19 mortality and YLL to the pre-COVID leading mortality causes. Comparative observations were made between positive and mortality cases stratified by age groups in relation to the cumulative vaccination doses. Results: The elderly were cocooned during the first wave (CFR 0.98) through the Vulnerable Act, with only 10.80% of positive cases and seven out nine deaths above 65 years. The Vulnerable Act was not reinstated again, with 13.68% of positive cases and 91.34% ( n = 369) of deaths above 65 years during the second wave (CRF 1.39). The elderly were given priority in COVID-19 vaccination rollout leading to an inverse relationship between positive cases/mortality and vaccination coverage. Conclusion: The elderly should be protected with timely restrictions to reduce morbidity, mortality and burden on healthcare systems. Vaccination is key to protecting the elderly, although mitigation measures, such as physical distancing, are still required to prevent the resurgence of infections and hospitalizations, especially in this group.